Mortality in Correctional Institutions: State Prisons, 2001-2017 ([Verlag nicht ermittelbar], 2021)
Mortality in Correctional Institutions (MCI) (formerly, the Deaths in Custody Reporting Program (DCRP)), is an annual data collection conducted by the Bureau of Justice Statistics (BJS). The MCI collection began in 2000 under the Death in Custody Reporting Act of 2000 (P.L. 106-297). It is the only national statistical collection that obtains detailed information about deaths in adult correctional facilities. MCI collects data on persons dying in state prisons, local jails and in the process of arrest. Each collection is a separate subcollection, but each is under the umbrella of the MCI collection. This deals with the prison subcollection, which has a prison death file. The prison portion of Mortality in Correctional Institutions began in 2001 after the passage of the Deaths in Custody Reporting Act of 2000 in October of 2000. The prison component of MCI collects data on inmate deaths occurring in the 50 state departments of corrections while inmates are in the physical custody of prison officials.